Activation of SOCS-3 by Resistin - Steppan, Claire M. (American Society for Microbiology, 2005)
Resistin is an adipocyte hormone that modulates glucose homeostasis. Here we show that in 3T3-L1 adipocytes, resistin attenuates multiple effects of insulin, including insulin receptor (IR) phosphorylation, IR substrate 1 (IRS-1) phosphorylation, phosphatidylinositol-3-kinase (PI3K) activation, phosphatidylinositol triphosphate production, and activation of protein kinase B/Akt. Remarkably, resistin treatment markedly induces the gene expression of suppressor of cytokine signaling 3 (SOCS-3), a known inhibitor of insulin signaling. The 50% effective dose for resistin induction of SOCS-3 is ∼20 ng/ml, close to levels of resistin in serum. Association of SOCS-3 protein with the IR is also increased by resistin. Inhibition of SOCS function prevented resistin from antagonizing insulin action in adipocytes. SOCS-3 induction is the first cellular effect of resistin that is independent of insulin and is a likely mediator of resistin's inhibitory effect on insulin signaling in adipocytes.